2015
DOI: 10.1007/978-3-319-22759-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Web Portals for Supply Chain Coordination: A Case Study

Abstract: The performance of the supply chains is highly linked with the quality of relationship between partners. Web portals are more and more used for facilitating this relationship, but the consequences of their implementation on real cases are still seldom analysed. Such analysis is provided in this communication, highlighting the interest but also the problems of supplier portals thanks to a questionnaire filled by more than 130 suppliers of a large company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
2
Order By: Relevance
“…More broadly, it is understood that the digitalization of a supply chain requires a high level of integration of the various partners' capabilities (Queiroz et al, 2021). However, the partners' use of these portals may not be as high as expected because suppliers have to work with many different tools and the focal firm may need to provide ongoing encouragement or pressure to facilitate assimilation (Garcia and Grabot, 2015;de Mattos and Laurindo, 2017). One of the challenges of such digital procurement projects consists in taking along suppliers and develop with them new interactions and knowledge (Handfield et al, 2019;Cox, 2022); the SECI model is well adapted to answer this issue.…”
Section: Supplier Portal Projectmentioning
confidence: 99%
“…More broadly, it is understood that the digitalization of a supply chain requires a high level of integration of the various partners' capabilities (Queiroz et al, 2021). However, the partners' use of these portals may not be as high as expected because suppliers have to work with many different tools and the focal firm may need to provide ongoing encouragement or pressure to facilitate assimilation (Garcia and Grabot, 2015;de Mattos and Laurindo, 2017). One of the challenges of such digital procurement projects consists in taking along suppliers and develop with them new interactions and knowledge (Handfield et al, 2019;Cox, 2022); the SECI model is well adapted to answer this issue.…”
Section: Supplier Portal Projectmentioning
confidence: 99%
“…Combined with the MVC architecture diagram, it can be seen that after the user sends an operation request by using the model module in the MVC architecture, the system can call the user's specific operation request by using the view module, and at the same time feed back user event information to the controller. e controller will further retrieve the processing task data in the model module, and display the feedback and specific content information retrieved to the system user through the view module [1][2][3][4][5][6] It can greatly satisfy the effective management of the current university teaching system.…”
Section: Mvc Architecturementioning
confidence: 99%
“…(1) The first stage mainly studies the integration of supply chain management and ecommerce: Garcia and Grabot [47] pointed out that e-platforms are increasingly focusing on relationship improvement as the performance of ECSC is closely related to the quality of partnerships; Ma and Xie [48] compared a dual-channel supply chain under uncertain demand and conducted a complexity analysis; Shao [49] studied the impact of transportation costs on the decision-making of the platform and the manufacturer in ECSC, then found that the platform is unprofitable when the manufacturer prefers free shipping. (2) The second stage mainly studies the operation and optimization of ECSC: Panda et al [50] discussed the pricing of high-tech products in the online and offline dual-channel supply chain, then designed a revenue-sharing coordination mechanism to achieve supply chain coordination; Jia and Li [51] studied the channel selection of the manufacturer when the e-platform can choose to provide services and self-operated stores, then found that the commission will affect the preferred mode of both the manufacturer and the e-platform; Yan et al [52] found that the e-platform providing financing services can expand the market share of the e-platform and increase the profitability of the system.…”
Section: Literature Reviewmentioning
confidence: 99%